2016
DOI: 10.1097/dcr.0000000000000576
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Active Long-term Problems in Patients With Anorectal Malformations: A Systematic Review

Abstract: There is an overall high prevalence of active long-term issues in adolescents and young adults with anorectal malformations. Additional multicenter research is needed to define characteristics and predictors of long-term outcome, to implement effective follow-up, and to transition to adult health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
32
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 34 publications
0
32
0
3
Order By: Relevance
“…It is increasingly recognized that continuing follow-up and transitional care of patients with complex problems, such as ARM or HD, is an essential part of health care [ 9 ]. Many authors have reported the need for a transitional outpatient clinic, or have described the need to define patients’ problems during the transition phase to facilitate the process of starting adult care [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is increasingly recognized that continuing follow-up and transitional care of patients with complex problems, such as ARM or HD, is an essential part of health care [ 9 ]. Many authors have reported the need for a transitional outpatient clinic, or have described the need to define patients’ problems during the transition phase to facilitate the process of starting adult care [ 9 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…These diseases are, respectively, caused by the incomplete or insufficient development of the anus or rectum ( Holschneider & Puri, 2008 ) or the absence of enteric nervous system along the intestine ( Amiel et al, 2008 ). Although ARM and HD are often diagnosed and treated during the neonatal period, patients often experience long-term gastrointestinal morbidity such as chronic incontinence, constipation, or defective bowel control ( Rigueros Springford et al, 2016 ; Rintala & Pakarinen, 2012 ; Stenström et al, 2014 ). In addition, psychological problems are frequently observed, such as shame due to fecal incontinence.…”
Section: Introductionmentioning
confidence: 99%
“…Sexual impairment could also be the result of postoperative problems, such as scar tissue, or constrictions in the genital area due to urogenital anomalies ( Athanasakos et al., 2006 ; Manderson, 2005 ; Witvliet et al, 2017 ). 1 These problems can negatively affect the sexual health of these patient groups ( Kyrklund et al, 2016 ; Rigueros Springford et al, 2016 ; van den Hondel et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, congenital GI tract atresia was a leading cause of neonatal surgical diseases in 2013 ( 2 ) . Due to medical advances, the mortality rate of children born with GI tract atresia has decreased year by year ( 3 ) ; however, related long-term morbidities, such as feeding gastrostomy or jejunostomy, short bowel syndrome, faecal and/or urinary incontinence, and chronic constipation ( 4 6 ) , continue to have a significant impact on childhood quality of life. In addition, occurrence of the condition typically increases the psychological and social burden on mothers, as well as on their partners and families due to concern for the child’s health.…”
mentioning
confidence: 99%